Super-Strong Photonic Localizations in Symmetric Defect Waveguide-Ring Networks - Xubo Hu; Xiangbo Yang; Dongmei Deng (IEEE Photonics Journal, 2017)
Super-strong photonic localizations that occur in symmetric defect waveguide-ring networks (SDWRNs) are presented in this study. It is found that the intensity of maximal photonic localization can increase as an exponential function with the number of rings and as a power function with the breaking degree of a defect in SDWRNs. Compared with previous reported results, SDWRNs can generate stronger photonic localizations and possess simpler structures. The fitting formulas of the intensity have been obtained. Moreover, the intensity, site number, and site positions for the maximal photonic localization can be adjusted by changing structural parameters in SDWRNs. The study may provide attractive applications as multichannel high efficiency energy storages, narrow-bandwidth filters, optical switches, and other correlative optical devices.